Modeling of Mass Transfer Process of Prolate Spheroidal Drops in Rotating Disc Contractor Column - Budiman, Herdi; Talib, Jamalludin (Journal of Science and Technology, 2012)
Several models have been developed for the modeling of Rotating Disc Contactor (RDC) columns. The modeling shows that the drop size distribution and the mass transfer processes are important factors for the column performances. Since the behavior of the drop breakage and the mass transfer process involve complex interactions between relevant parameters, the need to get as close as possible to the reality of the processes is evident. Several researchers have been working in this area. Most of these models have been studied based on the assumption of spherical droplets. The problem of spherical drop or bubble is known as the simplest and ideal case in which the problem can be considered in spherical coordinate system. However there are many physical situations the shape of the drops contained in liquid is not perfectly spherical, and may be classified as prolate or oblate spheroids. For most industrial applications particles encountered are irregular or non-spherical. In this research, the diffusion equation given in the prolate spheroidal coordinate system is used for a two-dimensional case. An analytical solution of the unsteady diffusion equation describing mass transfer for prolate spheroidal drops, considering a constant diffusion coefficient is presented. The resulting equations are analytically solved by using the Laplace transform method.